Combined Signature of the Fecal Microbiome and Metabolome in Patients with Gout - Shao, Tiejuan; Shao, Li; Li, Haichang; Xie, Zhijun; He, Zhixing; Wen, Chengping (Frontiers in Microbiology, 2017)
This study employed microbiome and metabolome analysis to explore the fecal signatures of gout patients. Fecal samples from 52 male individuals (26 healthy controls and 26 gout patients) were analyzed by 1H NMR spectroscopy and Illumina Miseq sequencing. The signatures of microbiome showed being up-regulation of opportunistic pathogens, such as Bacteroides, Porphyromonadaceae Rhodococcus, Erysipelatoclostridium and Anaerolineaceae. The signatures of metabolome were some altered metabolites which may involve uric acid excretion, purine metabolism and inflammatory responses. Meanwhile, the correlation between discrepant metabolites and microbial taxa indicated that they could be the combined signatures of gout. This study suggests that the combined analysis of the fecal microbiome and metabolome may effectively characterize diseases.